Quality of care for cardiopulmonary conditions : a review of the literature and quality indicators - Kerr, Eve A.; Asch, Steven M.; Hamilton, Eric G.; McGlynn, Elizabeth A.; Rand eBooks (Santa Monica, CA : RAND, 2000)
This report is one of five volumes providing detailed information on the QA Tools, RAND's comprehensive, clinically based system for assessing quality of care for children and adults. The QA Tools indicators encompass screening, diagnosis, treatment, and follow-up in 46 clinical areas and cover a variety of modes of providing care, including history, physical examination, laboratory study, medication, and other interventions and contacts. Development of each indicator was based on the ratings of a panel of experts in the relevant fields and on a focused review of the scientific literature, which is clearly documented for each clinical condition. This volume focuses on indicators for care of cardiopulmonary conditions. Each chapter summarizes the results of the literature review for a particular condition, provides RAND staff's recommended indicators based on that review, and notes the level of scientific evidence supporting each indicator along with the relevant citations. In addition, this work details the process by which the expert panel evaluated the indicators and the final disposition of each indicator. Clinical conditions covered in this volume are: Asthma, atrial fibrillation, cerebrovascular disease, chronic obstructive pulmonary disease, cigarette counseling, community-acquired pneumonia, coronary artery disease, heart failure, hyperlipidemia, hypertension, upper respiratory infections. Other RAND Health titles on the QA Tools system focus on indicators for general medicine, oncology and HIV, children and adolescents, and women.
Introduction -- Asthma -- Atrial Fibrillation -- Cerebrovascular Disease -- Chronic Obstructive Pulmonary Disease -- Cigarette Counseling -- Community-Acquired Pneumonia -- Coronary Artery Disease - Diagnosis and Screening -- Coronary Artery Disease - Prevention and Treatment -- Heart Failure -- Hyperlipidemia -- Hypertension -- Upper Respiratory Infections -- Appendix A: Panel Rating Sheets by Condition -- Appendix B: Crosswalk Table of Original and Final Indicators.
"RAND Health."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: Cardiopulmonary system -- Diseases -- Treatment -- Quality control; Managed care plans (Medical care) -- Quality control; Managed care plans (Medical care) -- Standards; Medical care -- Evaluation -- Methodology; Medical care -- Quality control; Electronic books